ARE BANKING INDUSTRY MORE RESILIENT AGAINST THE COVID-19 PANDEMIC IN INDONESIA? - Radia Purbayati; Agil Krisna Rivanda; Kurnia Fajar Afgani; Rosma Pakpahan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2022)
This research aims to examine the resilience of the banking industry due to Covid-19. The study focuses on Commercial Banks in Indonesia along January 2017 to April 2021. The study uses a descriptive analysis method of the banking industry in Indonesia with the variables tested including ROA, CAR, LDR, NPL, NIM and BOPO using VAR/VECM analysis. The results show that VECM modelling at the 2 nd lag optimum is used at this analysis. Variables that significantly affect banking performance in the short and long run are CAR, LDR, NPL, NIM, BOPO and ROA at 1 st lag, but at 2 nd lag the LDR variable has no significant effect on ROA in the short run. The shock caused by the variables CAR, LDR, NPL, NIM, BOPO and ROA itself is responded by ROA through the Impulse Response Function and will be corrected to ease moving towards early equilibrium (conditions before the Covid-19 pandemic) within a period of time recovery between 5 months to 30 months. Even though the banking industry is contracting and inefficiency has occurred due to the Covid-19 pandemic, the resilience of the banking industry is still maintained and under control due to the implementation of various stimulus policies issued by the OJK to mitigate banking risks during the Covid-19 pandemic which has the potential issues to financial distress.